The Effect Of Activation In Carbon Adsorbent On Adsoprtion And Desorption Processes Of LPG Gas - Herawan, Safarudin Gazali; Mohamad, Imran Syakir; Mohd Husin, Mohd Haizal; Yusof, Ahmad Anas; Suhaimi, Misha (2005)
Oil palm shells are an agricultural waste material found abundantly in Malaysia. Since the characteristics of oil palm shell were found suitable for preparing activated carbon, this material also has the potential to be prepared into other useful and valuable products. This research, the concern is to make use of oil palm shell to prepare the carbon adsorbent, which applied for LPG storage. This sample was prepared at a laboratory scale fixed-bed reactor, which is blanketed by a vertical furnace where pyrolysis took place. Nitrogen gas was used to obtain an inert atmosphere in the reactor. A suction blower was used to remove volatile matter as well as other gases during carbonization process. The samples were prepared in the different peak temperature and some of them were activated with CO2 activation, which was used to investigate the effect of it in the sample on adsorption and desorption processes. This research work will attempt to find a suitable solution to solve the environmental problems by utilizing the waste materials and to look into the industrial aspect of adsorption process for gas storage.